Effect of Weekly Antibiotic Round on Antibiotic Use in the Neonatal Intensive Care Unit as Antibiotic Stewardship Strategy - Wang, Bo; Li, Geng; Jin, Fei; Weng, Jingwen; Peng, Yaguang; Dong, Shixiao; Liu, Jingyuan; Luo, Jie; Wu, Hailan; Shen, Yanhua; Meng, Yao; Wang, Xiaoling; et al. (Frontiers in Pediatrics, 2020)
Background. Antibiotics are commonly used in the neonatal intensive care unit (NICU). The objective was to observe the effect of weekly antibiotic round in NICU (WARN) to the antibiotic use in NICU. Methods. A retrospective observational study was performed. Departmental-level diagnosis categories and the parameters of antibiotic usage in NICU for the period of 2016-2017 (Phase 1) and 2018-2019 (Phase 2) were collected. WARN in NICU was started since January 2018. A time series forecasting was used to predict the quarterly antibiotic use in Phase 2, based on data from Phase 1. The actual antibiotic use of each quarter in Phase 2 was compared with the predicted values. Results. Totally 9297 neonates were included (4743 in Phase 1, 4488 in Phase 2). The composition of the disease spectrum between Phase 1 and Phase 2 was not different (P >0.05). In Phase 1 and Phase 2, the overall antibiotic rate was 94.4% and 74.2%, the average accumulative defined daily dose per month was 199.00±55.77 and 66.80±45.64, the median antibiotic use density per month was 10.31 (9.00-13.27) and 2.48 (1.92-4.66), the median accumulative defined daily dose per case per month was 0.10 (0.09-0.13) and 0.03 (0.02-0.47), the number of patients who received any kind of antibiotic per 1000 hospital days per month was 103.45 (99.30-107.48) and 78.66 (74.62-82.77), rate of culture investigation before antibiotics was 64% to 92%, respectively, and all were better than the predicted values (P < 0.01). Conclusion. The implementation of periodical antibiotic rounds was effective in reducing the antibiotics use in the NICU.